Vocabulary improvement : words made easy - Bonet, Diana (Crisp Pub. Menlo ParkUS, 1992)
Provides tools for improving basic vocabulary and word-use skills in listening, speaking, reading and writing. Traces the development of the English Language and provides several examples of loanwords from other languages to the English vocabulary. Lists 5 techniques for learning new words, and explains how to use the dictionary and thesaurus. Shows how knowing the meanings of prefixes, suffixes and non-English roots helps in deciphering the meaning of words. Distinguishes between idioms, jargon and slang and shows how they enrich (and confuse/complicate) the language. Includes practice exercises and word games.